Determinants of Competitive Advantage and Their Impacts on Buyback Decisions (Case Study of Bu Tjondro's Kremes Chicken) - Rahayu Lestari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the efforts to increase competitive advantage and repurchase decisions at Bu Tjondro's Kremes Chicken Restaurant around South Tangerang. Sampling is based on Purposive criteria, with as many as 80 respondents using proportional random sampling. The analytical method used is statistical-partial least squares using the SmartPLS 3.0 software analysis tool. The study results show that digital marketing has a positive and significant effect on competitive advantage. Product quality has a negative and significant effect on competitive advantage. Price has a positive and significant effect on competitive advantage. The location has a positive but not significant effect on competitive advantage. Service quality has a positive and significant effect on competitive advantage. Product quality has a positive and significant effect on repurchase decisions. Price has a negative but significant effect on repurchase decisions. The location has a negative but not significant effect on repurchase decisions. Service quality has a positive and significant effect on repurchase decisions. Competitive advantage has a positive but not significant effect on repurchase decisions.